National Identity Through Prototypes and Metaphors: The Case of "Romanianness" - Razvan Sibii (Journal of Global Initiatives, 2012)
The last country God created was Romania. Realizing that he still had a lot of riches left over from the other countries, He let Romania have more natural treasures than anybody else. Seeing this, Saint Peter asked in surprise: "My Lord, why are you giving this country more riches than you've given to any other?" "Don't you worry," said the Lord, "Just wait 'till you see the people I will put in charge of those riches!..."